2018
DOI: 10.1302/0301-620x.100b4.bjj-2016-1098.r3
|View full text |Cite
|
Sign up to set email alerts
|

Displaced femoral neck fractures in patients 60 years of age or younger: results of internal fixation with the dynamic locking blade plate

Abstract: The rate of fracture healing after DLBP fixation of displaced femoral neck fracture in young patients is promising and warrants further investigation by a randomized trial to compare the performance against other contemporary methods of fixation. Cite this article: Bone Joint J 2018;100-B:443-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The results of this study showed a failure rate of 4% [13]. Another recent prospective cohort study of 106 patients of 60 years and younger with displaced FNF demonstrated a DLBP related failure rate of 13.2% [14]. However, randomized controlled trials are needed to provide high-level evidence to determine the value of DLBP.…”
Section: Introductionmentioning
confidence: 65%
“…The results of this study showed a failure rate of 4% [13]. Another recent prospective cohort study of 106 patients of 60 years and younger with displaced FNF demonstrated a DLBP related failure rate of 13.2% [14]. However, randomized controlled trials are needed to provide high-level evidence to determine the value of DLBP.…”
Section: Introductionmentioning
confidence: 65%
“…Stable internal fixation achieved with static compression of the fracture surfaces plays a key role in the treatment of femoral neck fractures . This is in contrast with diaphyseal long‐bone fractures, where cyclic fracture‐site micromotion is a desirable phenomenon to stimulate callus formation .…”
Section: Discussionmentioning
confidence: 99%
“…Stable internal fixation achieved with static compression of the fracture surfaces plays a key role in the treatment of femoral neck fractures. 4,8 This is in contrast with diaphyseal long-bone fractures, where cyclic fracture-site micromotion is a desirable phenomenon to stimulate callus formation. 30 Although stability is the primary goal of treatment, in vivo data on the stability of femoral neck fractures stabilized under internal fixation is still scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations